The Ethics of a Muslim While in the Bathroom Based on Ma'anil Hadith - Hafizul Fadli; Pathur Rahman; Sulaiman Muhammad Nur (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2025)
Bathrooms or toilets are an essential part of daily life, serving as places for personal cleansing and relieving oneself. In Islam, such activities are not only related to physical cleanliness but also to moral values and ethics emphasized in the hadiths of the Prophet Muhammad (peace be upon him). The purpose of this study is to analyze the proper manners and recommended practices for using the bathroom as stated in the Prophet’s hadiths, such as supplicating before entering, entering with the left foot, maintaining modesty, and following appropriate procedures when entering and leaving the bathroom. Through an examination of these hadiths, this study seeks to explore the deeper meanings behind Islamic teachings that regulate human behavior in everyday situations. The analysis is conducted by reviewing the religious, moral, and social contexts of each relevant hadith in order to understand why Islam places cleanliness and propriety as integral parts of faith. This research employs a qualitative approach based on library research to collect data. The approach involves engaging with relevant literature and ideas to draw conclusions. Muslims may gain new insights from the results of this study regarding the importance of good manners in all aspects of life, even in matters that may seem trivial, such as using the bathroom. Thus, this study affirms that both physical and spiritual cleanliness are tangible manifestations of the faith and discipline of a Muslim who strives to comprehensively follow the teachings of the Prophet Muhammad (peace be upon him).